Dividend Determinants of Indonesian Sharia Stocks List (Case Study for The Period of 2009-2017) - Farikha Amilahaq (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2019)
The study tried to help the Muslim investors and prospective Muslim investors deciding their investment plan in sharia firms, by seeking for the pattern of dividend policy which is the income sources of the Muslim investors. The data used are 33 companies listed in Sharia Stock List continuously for 9 periods, also consistent to distribute the dividend. As for the factors that probably can affect the dividend are cash position, debt to equity ratio, return on investment, and the institutional ownership. The study also used firm size as a control variable, and suspecting return on investment and institutional ownership as moderating variables for cash position and debt ratio in affecting the dividend policy. The result showed only institutional ownership can affect dividend policy directly, while cash position will be able to influence the policy by being moderated by the return on investment and institutional ownership. Therefore, the Muslim investor or prospective Muslim investors can consider more to the ownership structure of the firms before deciding their investment allocation. The study found out that the management along with the institutional shareholders as one of the major shareholders, has considering the shareholders’ rights as well. The policy taken is intended not only to keep the shareholders’ need of the return of their investment, but also to keep the Muslims’ shares of the firms still safe and stand on the good price.